2016
DOI: 10.1007/s00216-016-9911-3
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the determination of peak distribution across a two-dimensional separation space for the identification of optimal column combinations

Abstract: For the identification of the optimal column combinations, a comparative orthogonality study of single columns and columns coupled in series for the first dimension of a microscale two-dimensional liquid chromatographic approach was performed. In total, eight columns or column combinations were chosen. For the assessment of the optimal column combination, the orthogonality value as well as the peak distributions across the first and second dimension was used. In total, three different methods of orthogonality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Leonhardt and co-workers investigated the performance of different orthogonality metrics. 84 They noted that the convex hull and bin-counting methods do not provide information on the peak distribution, whereas the asterisk method does not work optimally when only a limited number of components are used for method development. The authors therefore introduced a new concept for peak distribution assessment across the separation space of two-dimensional separation systems in combination with clustering detection.…”
Section: Methods Development and Optimization Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Leonhardt and co-workers investigated the performance of different orthogonality metrics. 84 They noted that the convex hull and bin-counting methods do not provide information on the peak distribution, whereas the asterisk method does not work optimally when only a limited number of components are used for method development. The authors therefore introduced a new concept for peak distribution assessment across the separation space of two-dimensional separation systems in combination with clustering detection.…”
Section: Methods Development and Optimization Strategiesmentioning
confidence: 99%
“…Work has also been invested in studying some of the quality descriptors themselves. Leonhardt and co-workers investigated the performance of different orthogonality metrics . They noted that the convex hull and bin-counting methods do not provide information on the peak distribution, whereas the asterisk method does not work optimally when only a limited number of components are used for method development.…”
Section: Methods Development and Optimization Strategiesmentioning
confidence: 99%
“…However, it is important to develop appropriate method through a rigorous selection of such chromatographic parameters as stationary and mobile phases, column formats, and chromatographic conditions [151]. One of the most important parameters to be assessed is the orthogonality of single and coupled columns, necessary for the determination of the optimal column combination [153].…”
Section: Chromatographic Conditionsmentioning
confidence: 99%
“…The authors found that the asterisk metric is less affected by a change in the number of compounds, unlike, for example, the bin-counting approaches, and that its value is less affected by outliers than the convex-hull strategies. More recently, new metrics were developed by Mani-Varnosfaderani and Ghaemmaghami, based on the maximal information coefficient [261], and by Leonhardt et al [262], based on a combination of bin-counting and calculated histograms for the respective dimensions. Mommers and Van der Waals [263] developed two new metrics based on a polynomial fit and a new bin-counting approach.…”
Section: Quality Descriptorsmentioning
confidence: 99%
“…Two metrics for measuring orthogonality for 2D chromatography 2D separations 2019 [263] The role of surface coverage and orthogonality metrics for 2D chromatography 2D separations 2017 [249] New method for the determination of peak distribution across a 2D separation space for optimal column combinations 2D separations 2016 [262] Comparison of orthogonality metrics by statistical analysis 2D separations 2015 [257] Comparison of orthogonality estimation methods for the 2D separation of peptides 2D separations 2015 [256] Assessment of the orthogonality in 2D separative systems using criteria defined by the maximal information coefficient 2D separations 2015 [261] Asterix equation: A new measure of orthogonality 2D separations 2014 [258] Assessment of 2D separative systems using the nearest neighbour distances approach. Part 1: Orthogonality 2D separations 2013 [278] A modelling approach for orthogonality of comprehensive 2D separations 2D separations 2013 [259] Fractional coverage metrics based on ecological home range for calculating the effective peak capacity 2D separations 2012 [253] The dimensionality of chromatographic separations 2D separations 2011 [252] Orthogonality of 2D separations based on conditional entropy 2D separations 2011 [254] Informational orthogonality of 2D chromatographic separations 2D separations 1996 [250] Geometric approach to factor analysis for the estimation of orthogonality and practical peak capacity 2D separations 1995 [260] Optimization of GC × GC method based on orthogonality GC × GC 2018 [264] Convex Hull: A new method to determine the used separation space GC × GC 2010 [251] Protocols for finding the most orthogonal dimensions for LC × LC LC × LC 2015 [265] Orthogonality measurement for multi-dimensional chromatography in three and higher dimensional separations…”
Section: Subcategory Year Referencementioning
confidence: 99%